Inside the impulsive brain: a narrative review on the role of neurobiological, hormonal and genetic factors influencing impulsivity in psychiatric disorders - Hannah Raji; Susha Dinesh; Sameer Sharma (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery)
Abstract This abstract delves into the intricate nature of impulsivity and its ramifications across psychiatric disorders, leveraging advancements in neuroimaging and psychological studies. It elucidates diverse facets of impulsivity, encompassing response, choice, and tendencies, emphasizing its pivotal role in executive functioning and social development. The intricate interplay of hormonal influences, specifically cortisol, adrenaline, and testosterone, is meticulously examined, unveiling associations between elevated cortisol levels, excessive adrenaline release, and heightened impulsivity. The ventromedial prefrontal cortex (VMPFC) assumes a central role in decision-making and emotional regulation, demonstrating correlations with conditions, such as antisocial behavior and mood disorders. Substantial contributions from neurotransmitters like dopamine and serotonin to impulsive behavior underscore the imperative need for genetic and neurochemical investigations to identify factors crucial for effective management. Interconnections between stress, impulsivity, and decision-making are accentuated, particularly in mood disorders. Hormones, such as leptin and ghrelin, in conjunction with the hypothalamic–pituitary–adrenal axis, play pivotal roles in conditions like major depressive disorder. Concurrently, leptin resistance exerts influence over appetite and mood regulation. The nexus between impulsivity and substance use disorders emphasizes the intricate involvement of neurobiological, neurotransmitter, and genetic components, guiding targeted interventions. Recognition of gender-specific impulsive behaviors and hormonal influences is imperative for tailoring treatment plans. Advocating a comprehensive approach that integrates hormonal assessments with clinical evaluations, taking into account the neurobiological context, is essential. While serotonin systems show promise for treating impulsive aggressiveness, challenges encompass intricate hormonal interactions, ethical considerations, limited treatment options, and the necessity for individualized approaches. Addressing these intricacies is pivotal for advancing knowledge and formulating effective interventions for Impulsive Control Disorders.